2009
DOI: 10.1086/596504
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Multiclass Drug–Resistance in HIV‐2 in Antiretroviral‐Treated Individuals in Senegal: Implications for HIV‐2 Treatment in Resouce‐Limited West Africa

Abstract: Background The efficacy of various antiretroviral (ARV) therapy regimens for human immunodeficiency virus type 2 (HIV-2) infection remains unclear. HIV-2 is intrinsically resistant to the nonnucleoside reverse-transcriptase inhibitors and to enfuvirtide and may also be less susceptible than HIV-1 to some protease inhibitors (PIs). However, the mutations in HIV-2 that confer ARV resistance are not well characterized. Methods Twenty-three patients were studied as part of an ongoing prospective longitudinal coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 36 publications
(34 reference statements)
3
70
0
1
Order By: Relevance
“…A rapid emergence of mutations potentially associated with drug resistance has been reported for HIV-2 ϩ patients under ART (25,29,41). We confirmed the presence of mutations in the reverse transcriptase and protease in our ART-treated HIV-2 cohort (Table 4).…”
Section: Relationship Of Plasma and Cell-associated Viral Load With Csupporting
confidence: 83%
“…A rapid emergence of mutations potentially associated with drug resistance has been reported for HIV-2 ϩ patients under ART (25,29,41). We confirmed the presence of mutations in the reverse transcriptase and protease in our ART-treated HIV-2 cohort (Table 4).…”
Section: Relationship Of Plasma and Cell-associated Viral Load With Csupporting
confidence: 83%
“…This could be due to differences in the assay used to determine drug susceptibility. Although there was no evidence for ABC resistance mediated by K65R in these in vitro studies, in vivo, the mutation was reported to be selected in HIV-2-infected patients experiencing virological failure while receiving an ABC-containing regimen (14,15,20). In both in vitro studies, mutation K65R was introduced in the HIV-2 ROD9 background, which suggests that variations or mutations present in the patient isolates contribute to resistance mediated by the K65R mutation.…”
Section: Figmentioning
confidence: 89%
“…In HIV-2 patients failing therapy, V111I was previously reported to be coselected with mutation Q151M (14,15,20). Mutation Q151M alone was suggested to confer resistance to d4T and ABC, whereas resistance to other NRTIs would involve the coselection of V111I (20).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations